Additions to the Cyperaceae of Madhya Pradesh - Sahni, K. C.; Vaid, K. M.; Naithani, H. B. (Indian Forester, 1972)
A comprehensive account of the "Cyperaceae of Madhya Pradesh" published by Tiwari and Maheshwari lists 97 species. The present paper records six more species as additions to the earlier enumeration. These are-Cyperus cephalotes Vahl, C. melanospermus (Nees) V. Suringar, Eleocharis geniculata (L.) Roem.& Sch., Fimbristylis acuminata Vahl, F. eragrostis (Nees) Hance and Scleria rugosa R. Br.